THE VALUE RELEVANCE OF INTELLECTUAL CAPITAL AND OWNERSHIP STRUCTURE ON THE SMES PERFORMANCE - Hartati, Noorina; Dwiyani Hadiwidjaja, Rini (LPPM Universitas Terbuka, 2019)
Intellectual Capital (IC) consists of VACA (CE), VAHU (HC), STVA (SC), Ownership Managerial (OM), and Institutional Ownership (OI). This study aims to examine whether Intellectual Capital (IC) has a positive effect on company performance, which is proxied by ROA and ROE, with the Leverage and Total Assets as control variables. Specifically, the researcher tested eight (8) hypotheses using multiple linear regression (p-values). The results of multiple linear regression tests (p-value) show that the variables VACA (CE), VAHU (HC), STVA (SC), and Intellectual Capital (VAICtm) have a positive effect on SMEs financial performance, both with ROA and ROE proxies. However, Ownership Managerial (OM) and Ownership Institutional (OI) variables do not affect both ROA and ROE. Then for the control variable, leverage affects ROA, while Total Assets affect ROE. Therefore, the research further strengthens previous studies that Intellectual Capital and its components, which include Employed Capital, Human Capital, and Structural Capital, affect SME's financial performance, both through ROA and ROE. VAICTM is the best indicator to measure IC (Intellectual Capital). The improvement of the financial performance of Small and Medium Enterprise (SMEs), it is necessary to pay attention to their employees (HC), capital structure (CE), and organizational structure in the company (SC).